Peran Dinas Perhubungan Kota Bandung Dalam Tata Kelola Perparkiran - Maharani, Nadya Puan; Rahmatullah, Aji; Zuhri, Muhammad Alfian; Afifah, Dian Fitriani (CV. Rayyan Dwi Bharata, 2025)
The division of power in Indonesia consists of two dimensions: vertical and horizontal. Horizontally, power is separated among the executive, legislative, and judicial branches by applying the principle of checks and balances. Vertically, power is divided between the central government and regional governments through the principle of decentralization, as regulated in Law No. 23 of 2014 on Regional Government. Regional governments aim to manage governmental affairs at the local level. Regional governmental affairs are classified into absolute affairs, concurrent affairs, and general affairs. Concurrent affairs are managed jointly by the central and regional governments, including areas such as education, health, and transportation. The Department of Transportation (Dishub) is responsible for managing transportation affairs at the regional level, including addressing illegal levies (pungli) in illegal parking areas. This practice of pungli often occurs in illegal parking lots and causes public distress. To tackle this, Dishub conducts regular patrols, community outreach, installs electronic parking meters, and forms the Clean Sweep Task Force (Saber) to combat pungli. These measures aim to enhance transparency, optimize Local Revenue (PAD), and restore public trust in local governments. This study uses a qualitative method to analyze the role of Dishub in addressing pungli in illegal parking areas through government instruments in Hughes' theory. This method allows for data collection through observation, interviews, and documentation from relevant parties, such as Dishub officers, parking attendants, and the public. The research is expected to provide a clearer picture of the steps taken by Dishub to create an effective and accountable parking management system. Thus, pungli practices can be minimized, parking governance becomes more orderly, and greater benefits can be provided to the public and regional governments.